2009
DOI: 10.1603/033.046.0525
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infection ofLutzomyia neivaiandLutzomyia sallesi(Diptera: Psychodidae) byLeishmania infantum chagasiin Brazil

Abstract: Natural infections with Leishmania were found in females of the phlebotomine sand flies Lutzomyia neivai (Pinto) (= Nyssomyia neivai) and Lutzomyia sallesi (Galvão & Coutinho) (= Evandromyia sallesi) (Diptera: Psychodidae) from Lassance, in the Brazilian state of Minas Gerais. Promastigotes were found in the pyloric region of the former species and in the abdominal midgut of the latter species. Insects found to be infected by microscopic examination were macerated in saline solution and inoculated into hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 39 publications
2
53
0
4
Order By: Relevance
“…Nyssomyia whitmani was only captured at the edge of the forest (Table II). Both species are involved in the transmission of Leishmania protozoa in Brazil (Andrade Filho et al 2007;Pita-Pereira et al 2009;Marcondes et al 2009;Saraiva et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Nyssomyia whitmani was only captured at the edge of the forest (Table II). Both species are involved in the transmission of Leishmania protozoa in Brazil (Andrade Filho et al 2007;Pita-Pereira et al 2009;Marcondes et al 2009;Saraiva et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the sandfly fauna have recorded 19 species in Lassance and Corinto and important vec- (Saraiva et al 2009). Some authors have reported alternating dominance of one of the two species in places where they occur in sympatry (Andrade Filho et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…intermedia suggest that it also is associated with Leishmania transmission in this region. Both species have been found to be naturally infected with Leishmania and are associated with ATL foci (Forattini et al 1972, Rangel et al 1984, Casanova et al 1995, Córdoba-Lanus et al 2006, Marcondes et al 2009, Saraiva et al 2009, Pita-Pereira et al 2009, Margonari et al 2010, Oliveira et al 2011, thereby demonstrating the great epidemiological importance of these species. Lutz and Neiva (1912) have reported that Ny.…”
Section: Discussionmentioning
confidence: 99%
“…2007;Pita-Pereira et al 2005). As espécies do complexo cortelezzii, recentemente encontradas naturalmente infectadas (Carvalho et al 2008;Saraiva et al 2009), também merecem mais investigações.…”
Section: Discussionunclassified